Anthropometric measures, endogenous sex steroids and breast cancer risk in postmenopausal women: a study within the EPIC cohort. - Rinaldi, S; Key, T; Peeters, P; Lahmann, P; Lukanova, A; Dossus, L; Biessy, C; Vineis, P; Sacerdote, C; Berrino, F; Panico, S; Tumino, R; et al. (2006)
In a large case-control study on breast cancer risk and serum hormone concentrations, nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort, we examined to what extent the relationship of excess body weight with breast cancer risk may be explained by changes in sex steroids. Height, weight, waist and hip circumferences, and serum measurements of testosterone [T], androstenedione [Delta4], dehydroepiandrosterone sulphate [DHEAS], estradiol [E2], estrone [E1] and sex-hormone binding globulin [SHBG] were available for 613 breast cancer cases, and 1,139 matched controls, who were all menopausal at the time of blood donation. Free T [fT] and free E2 [fE2] were calculated using mass action equations. Breast cancer risk was related to body mass index (BMI) (RR = 1.11 [0.99-1.25], per 5 kg/m2 increase in BMI), and waist (RR = 1.12 [1.02-1.24], per 10 cm increase) and hip circumferences (RR = 1.14 [1.02-1.27], per 10 cm increase). The increase in breast cancer risk associated with adiposity was substantially reduced after adjustment for any estrogens, especially for fE2 (from 1.11 [0.99-1.25] to 0.99 [0.87-1.12], from 1.12 [1.02-1.24] to 1.02 [0.92-1.14] and from 1.14 [1.02-1.27] to 1.05 [0.93-1.18] for BMI, waist and hip circumferences, respectively). A modest attenuation in excess risk was observed after adjustment for fT, but the remaining androgens had little effect on the association of body adiposity with breast cancer. Our data indicate that the relationship of adiposity with breast cancer in postmenopausal women could be partially explained by the increases in endogenous estrogens, and by a decrease in levels of SHBG.